2010
DOI: 10.1371/journal.pone.0012466
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Immunogenicity of Stabilized Trimeric Soluble Influenza Hemagglutinin

Abstract: BackgroundThe recent swine-origin H1N1 pandemic illustrates the need to develop improved procedures for rapid production of influenza vaccines. One alternative to the current egg-based manufacture of influenza vaccine is to produce a hemagglutinin (HA) subunit vaccine using a recombinant expression system with the potential for high protein yields, ease of cloning new antigenic variants, and an established safety record in humans.Methodology/Principal FindingsWe generated a soluble HA (sHA), derived from the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
124
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(133 citation statements)
references
References 41 publications
8
124
1
Order By: Relevance
“…These earlier HA-structural studies did not describe the oligomerization signal in the HA1 globular domain identified in the present study, suggesting that in the presence of HA2 the N-terminus ␤-sheet structure is engaged in an HA1-HA2 bridge and not in HA1 oligomerization. This may explain why most recombinant HA ectodomain proteins exist as monomers and require the addition of multimerization sequences such as "foldon" at the C terminus in order to produce stable oligomeric structures (3,28,29). This was further confirmed in a recent study in our laboratory with bacterially expressed HA proteins from the novel H1N1 A/California/04/2009 comparing the composition and immunogenicity of globular HA1 to that of the HA ectodomain (1-480).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…These earlier HA-structural studies did not describe the oligomerization signal in the HA1 globular domain identified in the present study, suggesting that in the presence of HA2 the N-terminus ␤-sheet structure is engaged in an HA1-HA2 bridge and not in HA1 oligomerization. This may explain why most recombinant HA ectodomain proteins exist as monomers and require the addition of multimerization sequences such as "foldon" at the C terminus in order to produce stable oligomeric structures (3,28,29). This was further confirmed in a recent study in our laboratory with bacterially expressed HA proteins from the novel H1N1 A/California/04/2009 comparing the composition and immunogenicity of globular HA1 to that of the HA ectodomain (1-480).…”
Section: Discussionmentioning
confidence: 62%
“…More recent publications emphasized the importance of high-MW oligomers for optimal immunogenicity of influenza virus recombinant HA proteins. Trimerization domains such as GCN4-pII and foldon were added to the C termini of HA ectodomains produced in mammalian or insect cells in order to produce stable oligomeric structures and to elicit optimal neutralizing antibody titers (3,28,29). On the other hand, our study demonstrates oligomer formation with bacterially expressed HA1 with no requirement for the addition of any foreign trimerization sequence.…”
Section: Discussionmentioning
confidence: 94%
“…For this purpose, we employed a water-soluble, non-cleavable, homobifunctional amine-reactive cross-linker BS3 with a history of successful use in stabilizing protein structures [10][11][12][13] . Figure 5 shows the chemical formula of BS3 and its cross-linking reaction with free epsilon amino groups of lysine in Strep-Tactin.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the immunogenicity caused by direct expression of the major vaccine antigen HA protein is often low, requiring large doses of vaccines to generate a level of seroconversion consistent with protection (25,26). Because of the importance of structure-based antigen, oligomeric HA is more efficient than monomeric HA (27). However, oligomerization is usually ensured through the addition of an extraneous sequence of unknown risk for human immunization.…”
Section: Discussionmentioning
confidence: 99%